2013
DOI: 10.1021/jo402313c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optoelectronic Properties of 6,12-Bis(amino)anthanthrene Derivatives

Abstract: A series of 6,12-bis(amino) anthanthrene-based conjugated molecules were prepared and characterized using UV-vis and fluorescence spectroscopy and cyclic voltammetry. The absorption spectra and redox potentials of these molecules can be modulated by changing the conjugated moieties linked at the 4 and 10 positions. Moreover, the optoelectronic properties of these derivatives strongly depend on the moieties attached to the nitrogen atoms at the 6 and 12 positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…In these cases the target azaacene core was first obtained in one step and then functionalized with solubilizing side groups such as triisopropylsilylethynyl by forming a −C≡C− linkage with the core in a second step . Compounds in which other groups link the solubilizing side chain with the core, such as −CH 2 NH− and −CH=N−, were also synthesized . Recently, bis‐tetracene diketone, first reported in 1949, to which two triisopropylsilylethynyl groups were attached, was used as a substrate in the synthesis of several acenes, and gave good solubility of the functionalized semiconductors in organic solvents …”
Section: Introductionmentioning
confidence: 99%
“…In these cases the target azaacene core was first obtained in one step and then functionalized with solubilizing side groups such as triisopropylsilylethynyl by forming a −C≡C− linkage with the core in a second step . Compounds in which other groups link the solubilizing side chain with the core, such as −CH 2 NH− and −CH=N−, were also synthesized . Recently, bis‐tetracene diketone, first reported in 1949, to which two triisopropylsilylethynyl groups were attached, was used as a substrate in the synthesis of several acenes, and gave good solubility of the functionalized semiconductors in organic solvents …”
Section: Introductionmentioning
confidence: 99%
“…[18] While searching for new biradical molecules, we used the anthanthrone core as as tartingp oint. [21] Then, aC asto-Stephen-Sonogashira coupling using triisopropylsilylacetylene (TIPSA) with compound 1 or compound 2 in toluenea fforded compounds 3 and 4 respectively,b oth in 99 %y ield. [19] It has been previouslyd emonstrated that anthanthronec an form as table biradical in an excited state by mechanochemistry on the solid sample (Figure 1, top).…”
mentioning
confidence: 99%
“…Thus, the extension of conjugation through these positions has only a slight effect on the band gap (high dihedral angle) . We have shown that the dihedral angle between anthanthrene and other π‐conjugated units can be reduced by forming intramolecular H‐bonding, but this strategy required the presence of an heteroatom directly attached to the anthanthrene, which limits the choice of functional groups that can be used to modulate the electronic properties …”
Section: Zigzag‐edged Pahs For Oscsmentioning
confidence: 99%